EFEKTIVITAS MODEL SUPERVISI AKADEMIK BERBASIS COACHING MOTIRTAR - Erik Wahyudi; Sri Utaminingsih; Erik Aditia Ismaya (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The implementation of academic supervision at elementary schools in Nalumsari did not run optimally. The problems came from the teacher’s low performance of teachers in managing learning in the classroom, the lack of teacher comfort when adapting to the supervision applied by the principal, the lack of teacher ability in analyzing the learning successfully, the lack of teacher ability to represent the self-reflection, and the lack of guidance carried out by the principal as follow-up supervision that could help teachers to improve their performance. Hence, this article analyzes the effectiveness of the Motirtar coaching-based academic supervision model. The research is a Research and Development to analyze the effectiveness of the development of the Motirtar coaching-based academic supervision model for elementary school teachers in Nalumsari. Data were collected by observation, documentation, interviews, and questionnaires. Data were analyzed through qualitative descriptive analysis, n-gain test, and t-test at a significance level of 0.05. The effectiveness of the Motirtar coaching-based academic supervision model was applied through product trials conducted at SDN 2 Gemiringlor, SDN 3 Ngetuk, SDN 1 Nalumsari, and SDN 1 Tunggul as an experimental class. SDN 2 Gemiringkidul, SDN 3 Bendanpete, SDN 2 Karangnongko, and SDN 2 Blimbingrejo are the control class. The results showed the effectiveness of the MOTIRTAR coaching-based academic supervision model to improve teacher performance as seen from the increasing value from first and final supervision in the control and experimental classes were Sig (2-tailed) 0.491 > 0.05 with an average value of 29.61 and 41,43.